THE INFLUENCE OF TEACHERS’ PEDAGOGICAL ON THE LEARNING QUALITY OF PUBLIC JUNIOR HIGH SCHOOLS IN REMBANG SUBDISTRICT - Nuraini; Titik Haryati; Sumarno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the effect of teachers’ pedagogical competence on learning quality in public junior high schools (SMP Negeri) in Rembang Subdistrict. The 2024 Education Report Card reported an average learning quality score (68.14) below the tuntas madya threshold (80.42), indicating the need for competency improvement. Employing a quantitative explanatory design, data were collected from 145 teachers in six schools through proportional random sampling. A validated and reliable Likert-scale questionnaire (Cronbach’s Alpha > 0.90) measured both variables. Data analysis using simple linear regression showed that pedagogical competence significantly and positively affects learning quality (β = 1.520, p = 0.013), explaining 42.0% of its variance (R² = 0.420). Teachers with high pedagogical competence marked by adaptive planning, effective strategies, and accurate assessment achieved better learning outcomes. The study highlights pedagogical competence as a key determinant of learning quality and recommends broader research with additional variables such as technology integration and school climate.